Using Google Scholar and Mendeley (GSM) to Improve The Ability to Write Scientific Articles from The Results of Teachers Classroom Action Research at SMPN 2 Balongbendo Sidoarjo - Ilmatus Sa’diyah; Abdul Hamid; Gading Adian Kun Saidan; Jafni Fara Zahirah; Nabila Eka Ramadhani (Nusantara Science and Technology Proceedings, 2023)
Classroom Action Research is research conducted through action in the classroom by teachers where the target or research subjects are students. Its application is to carry out and make reports on research results that can be written in the form of scientific articles, especially in the field of education. Classroom Action Research is a strategic way for teachers to increase professionalism in teaching and learning activities. In fact, there are teachers who don't know about the technicalities of implementing Classroom Action Research and writing scientific articles. This is also experienced by the teachers at SMPN 2 Balongbendo. Therefore, we do community service at SMPN 2 Balongbendo by applying Google Scholar and Mendeley (GSM) technology to improve the ability to write scientific articles from the results of classroom action research for teachers. In this community service activity, teachers are accompanied in using GSM technology to write scientific articles and publish them. Teachers are also given evaluations in the form of quizzes regarding the material that has been delivered by the service team. In addition, questionnaires were also distributed in the form of Google forms and the results showed that the teachers were very enthusiastic in participating in community service activities. Based on the results of the questionnaire, it was shown that 66.7% answered appropriate and 33.3% answered very appropriate regarding the suitability of the Mendeley and Google Scholar applications in improving the ability to write scientific articles for teachers.